2015
DOI: 10.1017/s0025315415001022
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology and life-history strategy of nesting males in a fish with long parental care, Lusitanian toadfish (Halobatrachus didactylus, Batrachoididae)

Abstract: The Lusitanian toadfish,Halobatrachus didactylus, like other batrachoidids, is a benthic fish species with nesting behaviour during the breeding season. During this prolonged period it engages in mating activities and remains in the nest providing parental care. It is not known whether males feed while providing parental care but it is likely that their limited mobility may restrict their diet and influence their fitness. As a consequence, egg cannibalism could occur as a life-history strategy. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…AccelTag proved to be a powerful tool to assess and monitor the fine-scale behaviour of a resident estuarine fish. In terms of ecological data obtained with AccelTag, the main findings are concordant with results obtained with other works that used distinct methodological approaches to study the Lusitanian toadfish foraging behaviour [21][22][23][24]. When comparing to other available tools (see [5] for further discussion) such as data storage tags with accelerometer sensors [6,7], and even more recent acoustic transmitters equipped with three-axis accelerometer sensors [8-11, 25, 26], the AccelTag has the advantage of being able to process the fine-scale acceleration information autonomously and acoustically transmit the correspondent behaviour.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…AccelTag proved to be a powerful tool to assess and monitor the fine-scale behaviour of a resident estuarine fish. In terms of ecological data obtained with AccelTag, the main findings are concordant with results obtained with other works that used distinct methodological approaches to study the Lusitanian toadfish foraging behaviour [21][22][23][24]. When comparing to other available tools (see [5] for further discussion) such as data storage tags with accelerometer sensors [6,7], and even more recent acoustic transmitters equipped with three-axis accelerometer sensors [8-11, 25, 26], the AccelTag has the advantage of being able to process the fine-scale acceleration information autonomously and acoustically transmit the correspondent behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…The species is more active in late spring and early summer, concurring with the reproductive period [17,18]. It occupies a top position on the food web [19] and exhibits a high degree of trophic plasticity, adapting its feeding habits to prey availability reproductive needs [17,20,21]. The specimens of this species remain most of the time buried or concealed in crevices, adopting a camouflage and ambush mode of predation [22,23].…”
Section: Open Accessmentioning
confidence: 99%
“…However, numerous studies have not detected any relationship between cannibalism and brood parentage or cuckolder pressure [e.g. male common goby (Svensson et al ., 1998; Vallon & Heubel, 2016); male spottail darter, Etheostoma squamiceps (Bandoli, 2006); male sand goby (Svensson & Kvarnemo, 2007; Lissåker & Svensson, 2008); male Lusitanian toadfish (Félix et al ., 2016); male and female Neolamprologus caudopunctatus (Cunha‐Saraiva et al ., 2018)].…”
Section: Adaptive Hypothesesmentioning
confidence: 99%
“…Some correlational studies have found inconclusive or even opposing evidence for the energy reserves hypothesis [e.g. male sand goby, Pomatoschistus minutus (Klug et al ., 2006); male plainfin midshipman fish (Bose et al ., 2015); male Lusitanian toadfish, Halobatrachus didactylus (Félix et al ., 2016)], and some experimental diet manipulations have also failed to influence parent–offspring cannibalism [e.g. male three‐spined stickleback (Belles‐Isles & Fitzgerald, 1991); male fantail darter, Etheostoma flabellare (Lindström & Sargent, 1997); male sand goby (Kvarnemo, 1997); male beaugregory damselfish, Stegastes leucostictus (Payne et al ., 2002)].…”
Section: Adaptive Hypothesesmentioning
confidence: 99%
“…Although we used playbacks and not real boat passages, our field experiment mimicked a typical pattern of noise exposure by common ferry boats and small outboard engine boats in the Tagus estuary, pointing to marked detrimental fitness effects, even with only up to 2 weeks of noise exposure from two boat types and without the possible effect of low frequencies below c. 100 Hz. Toadfish parental males will likely experience a higher noise exposure from boating as parental care takes up to 3 months during which males stay in the nest to care for the eggs and defend the nest from takeovers or egg predation (Félix et al, 2016). Also, depending on the breeding site, they will be exposed to more boat noise sources, such as large cruisers, cargo vessels and dredgers (Vieira et al, 2021b), which tend to be louder (Hildebrand, 2009) and likely more impacting (Putland et al, 2018), not to mention other forms of anthropogenic noise (Vieira et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%